Metaphors of Anger in Contemporary Bahasa Indonesia: A Preliminary Study (LingPoet: Journal of Linguistics and Literary Research, 2020)
According to â€œtheâ€ definition, metaphors conceptualize an abstract noun (i.e. a noun that is relatively burdensome to construe like â€˜angerâ€™, â€˜loveâ€™, â€˜lifeâ€™, etc.) through a concrete one / ones. The first domain is called target, the latter is called source; and the link (mapping) between these two is based upon (1) a perceptual or / and (2) a culture-bound association. A prime example of a mixed type association could be sometimes, life (abstract) is like a boxing match (concrete): you have to push through lifeâ€™s hardships! Although voluminous data about the metaphors of anger in linguistically rather diverse languages (like Hungarian, American English, Spanish, etc.) are available, these publications do not cover the two linguÃ¦ francÃ¦ of the historical Nusantara, Bahasa Indonesia and Bahasa Melayu. According to the expertsâ€™ literature, anger is often and language-independently (!) conceptualized as â€˜a substance in a containerâ€™, as â€˜an opponentâ€™, as â€˜a weaponâ€™ or as â€˜an object belonging to someoneâ€™; however, the salience of these metaphors shows slight differences (KÃ¶vecses / Szelid / Nucz et al. 2015). In this paper, we will discuss whether anger is conceptualized similarly in Bahasa Indonesia. As there is a wide selection of words for anger / angry (marah, kesal, sebal, jengkel, gusar, ngegas, gondok, etc.) that represents diatopic and diastratic variations, and even semantic differences, we had conducted a frequency of occurrence analysis in Google to find the most salient term. Based on this very term, we performed interviews with ten native speakers, gathered metaphors, and, after a primary evaluation of the data, we classified them according to their respective metaphoric concept (â€˜substance in a containerâ€™, etc.). Subsequently, we also tried to identify culture- / language-specific metaphors or metaphoric patterns that yet cannot be found in the specialist literature, and looked at the reasons behind the existence of these metaphoric concepts.